The nucleotide usages significantly impact synonymous codon usage in Mycoplasma hyorhinis. (11th January 2021) - Wu, Yaqin; Jin, Li; Li, Yicong; Zhang, Derong; Zhao, Yongqing; Chu, Yuefeng; Ma, Zhong‐ren; Ma, Xiao‐xia; Shang, Youjun
Abstract: Five annotated genomes of Mycoplasma hyorhinis were analyzed for clarifying evolutionary dynamics driving the overall codon usage pattern. Information entropy used for estimating nucleotide usage pattern at the gene level indicates that multiple evolutionary dynamics participate in forcing nucleotide usage bias at every codon position. Moreover, nucleotide usage bias directly contributes to synonymous codon usage biases with two different extremes. The overrepresented codons tended to have A/T in the third codon position, and the underrepresented codons strongly used G/C in the third position. Furthermore, correspondence analysis and neutrality plot reflect an obvious interplay between mutation pressure and natural selection mediating codon usage in M. hyorhinis genome. Due to significant bias in usages between A/T and G/C at the gene level, different selective forces have been proposed to contribute to codon usage preference in M. hyorhinis genome, including nucleotide composition constraint derived from mutation pressure, translational selection involved in natural selection, and strand‐specific mutational bias represented by different nucleotide skew index. The systemic analyses of codon usage for M. hyorhinis can enable us to better understand the mechanisms of evolution in this species.